2013
DOI: 10.1111/cen.12366
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal status and outcome of bariatric surgery in obese men

Abstract: Obesity-related hypogonadotrophic hypogonadism is a reversible condition in the majority of obese men. It does not reduce the efficacy of bariatric surgery. Preoperative weight-adjusted normal values are recommended to avoid an incorrect diagnosis of hypogonadism in obese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…An increase in serum androgen levels (for both total testosterone and the free testosterone index), which was even higher than the increase in SHBG levels in men has been reported (134, 191). Normalization of serum testosterone levels after BS is associated with improved fertility in severely obese men.…”
Section: Non-metabolic Bs-induced Endocrine Alterationscontrasting
confidence: 51%
See 1 more Smart Citation
“…An increase in serum androgen levels (for both total testosterone and the free testosterone index), which was even higher than the increase in SHBG levels in men has been reported (134, 191). Normalization of serum testosterone levels after BS is associated with improved fertility in severely obese men.…”
Section: Non-metabolic Bs-induced Endocrine Alterationscontrasting
confidence: 51%
“…It is thought that the differences between obese subjects with normal gonadal function and those with hypogonadism might be determined by aromatase expression levels: MOSH would be induced when aromatase gene expression is elevated. By contrast, testosterone levels would remain within the normal range when aromatase expression levels are low (134). Similar to PCOS in obese women, MOSH is not a generalized condition in male obesity and underlying mechanisms are largely unknown.…”
Section: Non-metabolic Bs-induced Endocrine Alterationsmentioning
confidence: 99%
“…In fact, low-calorie diet, with a weight loss of 9.8% induced an average T increase of less than 3 nmol/L, whereas results with bariatric surgery, with a weight loss of 32%, were three times higher (almost 9 nmol/L). In the last few years, four additional reports have evaluated the effect of surgery-induced weight loss on T production (Mora et al, 2013, Aarts et al, 2014, Calderón et al, 2014, Mihalca et al 2014). In addition, an update of a previous series was published (Samavat et al, 2014).…”
Section: B) Clinical Intervention Studiesmentioning
confidence: 99%
“…In addition, an update of a previous series was published (Samavat et al, 2014). Hence, so far, 15 observational studies (Bastounis et al 1998, Mingrone et al, 2002, Globerman et al 2005, Alagna et al 2006, Hammoud et al 2009, Omana et al 2009, Reis et al, 2010, Pellitero et al 2012 Mora et al, 2013;Aarts et al, 2014;Calderón et al, 2014, Mihalca et al 2014and Samavat et al, 2014 are available enrolling overall 398 patients, with a mean follow-up of 54.7 weeks, mean BMI of 48.6 kg/m 2 and mean age of 42.1 years (Table 1).…”
Section: B) Clinical Intervention Studiesmentioning
confidence: 99%
“…In fact, large population-based studies using liquid chromatography-tandem mass spectrometry (LC-MS/MS) have reported lower estradiol levels in hypogonadal men compared with eugonadal men. 15 16 Indeed, increased estradiol levels have only been reported in extremely obese men, 17 18 suggesting that increased estradiol contributes to the development of hypogonadism only in extremely obese men.…”
Section: Mechanisms Involved In the Relationship Between Male Hypogonmentioning
confidence: 99%